2004
DOI: 10.1007/s10165-004-0280-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and efficacy of low-dose methotrexate in patients with rheumatoid arthritis

Abstract: This article evaluates the relationship between the pharmacokinetics of methotrexate (MTX), its efficacy in the treatment of rheumatoid arthritis (RA), and serum folic acid (FA) levels. The pharmacokinetics of MTX was studied in 29 patients with RA treated with low-dose MTX. The weekly dose of MTX was given orally at 2-4 mg every 12 h over a period of 24-36 h. Blood samples were taken 4 h after the first administration in any given week. A Bayesian method was used to estimate individual MTX pharmacokinetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Notably, MTX was commonly effective for arthritis in our patients, despite a lower C max than those values reported in Western countries. [11][12][13] Hiraga et al 8 reported that the mean C max of MTX after the fi rst administration of the week was 0.241 µmol/l, and demons trated the effi cacy of MTX. The relationship between the effi ciency of MTX and C max needs to be further studied in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, MTX was commonly effective for arthritis in our patients, despite a lower C max than those values reported in Western countries. [11][12][13] Hiraga et al 8 reported that the mean C max of MTX after the fi rst administration of the week was 0.241 µmol/l, and demons trated the effi cacy of MTX. The relationship between the effi ciency of MTX and C max needs to be further studied in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Shiozawa et al 7 demonstrated that the mean maximal serum MTX concentration was achieved at 1-2 h after the intake of the fi rst dose of the week, and the pharmacodynamics of the MTX of the Japanese patients was comparable with those overseas. Another group also showed the relationship between the serum MTX concentration 8 . Hiraga et alreported that the improvement of C-reactive protein (CRP) levels by MTX therapy signifi cantly correlated with the area under the concentration-time curve for MTX.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, they are unreliable for predicting the efficacy or toxicity of MTX in patients with RA 6–12. In contrast, MTX-PG concentrations in erythrocytes have been identified as a potentially promising biomarker associated with response to MTX in patients with RA and juvenile idiopathic arthritis 12–17.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of efforts to identify clinical biomarkers for MTX therapy have focused on measures of drug disposition. Despite a high degree of interindividual variability in plasma pharmacokinetics, plasma MTX has not been found to be consistently associated with drug response in inflammatory arthritis (), and is of limited utility as a tool for therapeutic drug monitoring in these patients. The realization that MTX is metabolized intracellularly through the addition of glutamate residues, similar to endogenous folates, forming pharmacologically active species, has resulted in efforts to correlate clinical response with MTX polyglutamate concentrations in red blood cells (RBCs) ().…”
mentioning
confidence: 99%